Material Montessori y nociones lógico-matemáticas en niños de preparatoria de la Escuela de Educación Básica Dr. Edison Calle Loaiza, de la ciudad de Loja, en el período 2022-2023 - Cacay Vivanco, Mary Alejandra (2023)
The logical mathematical notions constitute a necessary learning within early childhood education, as it is the fundamental basis for further learning; therefore, this research was carried out with the purpose of determining how Montessori material contributes to improve the logical mathematical notions in high school children. , a mixed approach was used since it allowed analyzing and collecting information, quantitatively with the results obtained from the application of the evaluation instrument, qualitatively through the checklist and anecdotal records. The scope was descriptive since it facilitated the obtaining of information on the variables and their description, the methods were used: inductive-deductive, in order to make the concrete analysis and reach conclusions based on valid information, the analytical- synthetic contributed to the construction of the theoretical framework and in this way give emphasis and relevance to the research topic raised, the design was quasi-experimental since the independent variable was directly manipulated to demonstrate the effectiveness of the dependent variable, the instrument applied Battery for the evaluation of Mathematical Competence (EVAMAT-0), designed for 5-year-old children, demonstrated the difficulties that 80% presented at the beginning in logical-mathematical notions at a very low level, after executing activities based on the material Montessori, it was verified that there was improvement in the children since 60% were located in the upper zone. Concluding that the use of Montessori materials was very effective when verifying in the final evaluation good results in the area of logical-mathematical notions, achieving that more than half of the children reduced these difficulties, by using these materials that allowed them to develop the senses. And acquire significant learning for their future life. Keywords: Montessori material, sensory games, logical-mathematics, child education